Theileria annulata Induced Secondary Hypoxia Causes Ischemic Myocarditis in Cattle Calves - Gupta, Kapil Kumar; Srivastava, Mukesh; Gupta, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Involvement of the myocardium in theileriosis is not a common phenomenon but is commonly ignored under field conditions due tolack of proper knowledge about the pathophysiology of the disease. In this study, the electrocardiographic (ECG) features and alterationin serum concentration of cardiac-specific biomarkers like cardiac troponin-I (cTnI) and creatinine kinase (CK-MB) were evaluated inhealthy (n=10) and theileriosis affected (n=12) cattle calves. There were alterations in the ECG features and serum concentrations ofcTnI and CK-MB in theileriosis-affected calves as compared to healthy ones. Electrocardiographic study in diseased animals revealedthe presence of Sinus tachycardia, 1st degree AV block, Atrial premature complex, Left atrial hypertrophy, and Right atrial hypertrophyin 91.66%, 33.33%, 16.67, 50.00%, and 50.00% cases, respectively. Serum concentrations of cardiac troponin-I in healthy and diseasedanimals were 0.144±0.119 ng/mL and 1.271±0.342 ng/mL respectively, while serum concentrations of CK-MB in healthy and diseasedanimals were 34.039±2.983 ng/mL and 49.710±3.332 ng/mL, respectively. Results showed alteration in standard electrocardiographicfeatures and change in normal serum concentration of cardiac biomarkers, both indicative of cardiac involvement in the clinical Theileriaannulata infection
Keywords: Arrhythmia; Cardiac troponin-; CK-MB; Electrocardiography; Theileriosis